Effectiveness of self-learning module on the knowledge and practices regarding foot care among type II diabetes patients in East Delhi, India - Devi, Reeta; Kapoor, Bimla; Singh, Mongjam Meghachandra (International Journal Of Community Medicine And Public Health, 2017)
Background: Promoting self-care practices forms the cornerstone of care among patients of type II diabetes specially foot care which is widely neglected by the patients. The present study explored the effectiveness of a self-learning module (SLM) on the knowledge and practices regarding foot care among type II diabetic patients (T2DM). Methods: An earlier house to house survey identified 340 type II diabetic patients in a residential area of East Delhi. The patients were divided into four groups consecutively each having 85 T2DM patients. The groups were randomized into intervention group with SLM and another as control. Pre and post-test evaluation (after three months) was done using pre-tested interview schedule on knowledge and practices regarding foot care. Chi-square, Mc Nemar’s test, ‘t’ test (paired and unpaired) were used for pre-post comparison of knowledge and practices. ‘p’ less than 0.05 was considered significant. Results: The age of the study subjects ranged from 20 to 80 years with similarity between intervention (SLM) and control groups in terms of distribution of various socio-economic and demographic variables (p>0.05). SLM was significantly effective than control group in increasing knowledge on aspects of effect of diabetes on foot (p<0.05), foot care and its steps (p<0.05). The mean pre-test score on foot care procedure were 9.55±3.33 in SLM and 9.04±3.55 in control groups. The mean score increased to 36.9±4.35 in SLM (p<0.001) and 9.37±3.84 (p=0.48) in control groups in post-test. Conclusions: SLM was effective in increasing knowledge and practices regarding foot care among type II diabetic patients in East Delhi.